PEDAGOGICAL CONFERENCE AND ITS SOLUTION (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article analyzes the essence, causes and methods of their elimination of pedagogical conflicts. The psychological and pedagogical aspects of positive resolution of conflicts between teacher and student, teacher and parent, colleagues in educational institutions will be highlighted. The article emphasizes the importance of pedagogical dialogue, compromise, empathy and creating a positive psychological environment.